Biodiversity dynamics of chironomid midges in high‐altitude lakes of the Alps over the past two millennia. Issue 6 (22nd July 2015) - Ilyashuk, Elena A.; Ilyashuk, Boris P.; Tylmann, Wojciech; Koinig, Karin A.; Psenner, Roland
Abstract: Climate change is one of the key drivers of changes in the biodiversity of the planet. There is, however, a general lack of long‐term data sets showing trends in taxonomic diversity of aquatic insects in high mountain environments particularly vulnerable to climate change. Using palaeolimnological techniques, we explored the changes in subfossil chironomid assemblages from three remote water bodies in the Eastern Alps, with the main focus on taxonomic turnover over different intervals of the late Holocene. Major changes in the assemblages coincided with shifts between different climate regimes and were mainly associated with the taxonomic shifts indicating the crossing ecological thresholds related to the ice‐cover duration in alpine lakes. Patterns of assemblage turnover through the past 2000 years differ between the study sites. Nevertheless, despite site‐specific differences in the physical setting and taxonomic composition, the study sites reveal substantial chironomid assemblage turnover (>1.0 SD) since AD 1850. The highest chironomid turnover (0.87 SD) over the last 30 years (AD 1980–2010), more than three times greater (0.26 SD) than in the previous 30 years, is observed in the lake situated at the highest elevation among the study lakes. Applying non‐linear structural equation modelling, we found that cold‐season (October–May) temperatures and therefore lake ice phenology are among the most important environment variables affecting the chironomid assemblages. The results of this study suggest that further climate warming will increase the risk of ecological alterations in remote Alpine freshwaters, including major shifts in chironomid fauna.